Application of perforated PEEK framework for improving strength of a bases of removable complete denture for maxilla (Fracture and Structural Integrity, 2025)
The paper presents the results of computer simulation of a hybrid removable complete dentures (RCD) of a maxilla and analysis of its stress–strain states (SSSs) under typical operational loads. For improving their strength and stiffness, it was proposed to reinforce a base made of polymethylmethacrylate (PMMA) with a perforated framework (technological holes for enhancing adhesion) made of polyetheretherketone (PEEK). In total, the SSS for 10 different models were analyzed, simulating the presence or absence of a reinforcing framework as well as its perforation, location in the base, adhesion between the components, and the deformation of the alveolar ridge. The key difference of the conducted computer simulation was the application of a virtual support of the RCD. Its deformation imitated changes in the alveolar ridge height, as well as the presence of more rigid areas corresponding directly to both alveolar ridge and a torus. The SSSs for the FE-models were calculated by the finite element method using the ‘ABAQUS’ software package. The effect of the PEEK framework position on the mechanical properties of the RСD was assessed. It was shown that the main reason for the base’s failure was its bending under the applied loads. However, the load-bearing capacity of the RСD could be increased by 20–40% by embedding of the PEEK framework as an additional layer of the base dome. The effect of variation in the base support conditions, simulating the degradation of the alveolar ridge caused by the bone tissue resorption, was analyzed. It was found that the load-bearing capacity of the RСD could vary within 10% in such cases. The perforation in the PEEK framework did not reduce significantly the mechanical properties of the RСD, but its adhesion to the PMMA base exerted a decisive effect on the operational performance.
Keywords: structural integrity; removable complete denture; Polymethylmethacrylate; Polyetheretherketone; additive manufacturing; prosthesis framework; failure criterion; interlayer adhesion